"Palace of the Mining Magnate" - Unkown (My University, 2011)
This Renaissance pile was typical of the ostentatious residences built by the wealthy of early Johannesburg. This victorian fantasy presented a glistening white spectacle on a hilltop in Jeppestown.
Part of the Cyril Stollof (M.I.A) collection.
Keywords: Jeppestown, Johannesburg, Victorian Architecture